2001
DOI: 10.1007/s004030100263
|View full text |Cite
|
Sign up to set email alerts
|

In situ expression of the costimulatory molecules CD80 and CD86 on Langerhans cells and inflammatory dendritic epidermal cells (IDEC) in atopic dermatitis

Abstract: The functional expression of costimulatory molecules on antigen-presenting cells may be a key event in the pathogenesis of atopic dermatitis (AD). Recently, the expression of CD86 (B7-2/B70) has been demonstrated on CD1a+ epidermal dendritic cells (DC) in AD lesions by immunohistological and functional analysis. Therefore, we sought to further characterize the in situ expression of costimulatory molecules on these cells, considering the two subpopulations of (1) CD1a+++/CD11b- Langerhans cells (LC) containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 27 publications
6
31
0
Order By: Relevance
“…Preliminary in vitro studies confirmed that this recombinant protein could bind both monocytes in PBMC and dog IgE, and enhanced allergen-induced lymphoproliferation in experimentally sensitized dogs. Previous reports including our study in dogs described enhanced expression of CD80 and CD86 in immune cells in allergic patients [13,16,21], suggesting the potential effectiveness of CTLA4-targeted vaccines for application in immunotherapy. Further investigation of this novel strategy will hopefully provide options for the treatment of allergic diseases.…”
Section: Discussionsupporting
confidence: 60%
“…Preliminary in vitro studies confirmed that this recombinant protein could bind both monocytes in PBMC and dog IgE, and enhanced allergen-induced lymphoproliferation in experimentally sensitized dogs. Previous reports including our study in dogs described enhanced expression of CD80 and CD86 in immune cells in allergic patients [13,16,21], suggesting the potential effectiveness of CTLA4-targeted vaccines for application in immunotherapy. Further investigation of this novel strategy will hopefully provide options for the treatment of allergic diseases.…”
Section: Discussionsupporting
confidence: 60%
“…Previously, epidermal DCs in inflammatory skin lesions (atopic dermatitis and psoriasis) have been classified as Langerhans cells, inflammatory dendritic epidermal cells (IDECs), and plasmacytoid DCs, by FACS techniques (28)(29)(30). Tip-DCs might contain the IDEC population because both express the integrin CD11c (unlike Langerhans cells).…”
Section: Discussionmentioning
confidence: 99%
“…In human tissues, both dermal and Langerhans DC express MHC class II and CD1a molecules, but only dermal DC express CD11b (22). These two types of tissue DC can be further differentiated by expression of Birbeck granules, Langerin, and E-cadherin on Langerhans cells and by expression of DC-SIGN on dermal DC.…”
Section: Discussionmentioning
confidence: 99%